A simple, affordable, and rapid visual CRISPR-based field test for sex determination of earlier porcine embryos and pork products - Tao, D.; Liu, J.; Li, Q.; Jiang, Y.; Xu, B.; Khazalwa, Emmanuel M.; Gong, P.; Xu, J.; Ma, Y.; Ruan, J.; Niu, L.; Xie, S. (Springer, 2023)
Sex selection technologies have immensely impacted swine production globally. Conventional earlier embryo sex identification methods require professional technicians and sophisticated laboratory instruments. Rapid on-site gender identification of porcine embryos and pork products remains challenging. In this study, we developed a CRISPR/Cas12a-based fluorescence visualization point-of-care sex determination test that is rapid, accurate and easy to implement on-site. The CRISPR/Cas12a assay coupled with either the polymerase chain reaction (PCR) or loop-mediated isothermal amplification (LAMP) employs precisely designed primers and single-guide RNAs targeting the sex-determining region Y (SRY) and the zinc finger protein X-linked (ZFX) genes. PCR and LAMP amplicons were cleaved with the subsequent generation of fluorescing products detectable with portable blue and ultraviolet light transilluminators. Approximately two copies per microliter of the ZFX and SRY genes were detected using the RApid VIsual CRISPR (RAVI-CRISPR) assay. This method is a sensitive, inexpensive, versatile, and point-of-care test. The technology has other potential applications like determining the sex of diverse livestock species, detecting livestock disease-causing pathogens and evaluating the quality of meat products.